2020
DOI: 10.33545/pathol.2020.v3.i1d.183
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of vesiculobullous lesions of the skin and the diagnostic utility of immunofluorescence

Abstract: Introduction: Vesicobullous disorders represent a heterogenous group of dermatoses with protean manifestations in which the primary lesion is a vesicle or a bulla on the skin or mucous membrane or both. These lesions can be extremely debilitating, may have serious sequelae, and even fatal, necessating early treatment and intervention to prevent further morbidity and mortality. Many of these blistering diseases mimic each other clinically, Histopathology together with immunofluorescence are used for diagnosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…In the present study, the mean age of patients was 45.09 years, which was compatible with other studies (12,17,18,21). The earliest age of disease onset was observed in EB and Darier.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the mean age of patients was 45.09 years, which was compatible with other studies (12,17,18,21). The earliest age of disease onset was observed in EB and Darier.…”
Section: Discussionsupporting
confidence: 92%
“…Friction blister 0 (0) 0 (0) 0 (0) 0 (0) 0 (0) 0 (0) 0 ( 0 study, the rarest one was papule (23). In the present study, lesions were more commonly observed on the upper limb and trunk, consistent with Tunisia and India studies (4,17). Also, the most common deposited Ig was IgG, compatible with the Mittal study (18).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our findings, they found bullous pemphigoid to be the most common vesiculobullous skin lesion (38.1%), followed by pemphigus vulgaris. They concluded that skin punch biopsy is a reliable technique to diagnose vesiculobullous skin lesions, with DIF as an adjunctive tool [ 4 ]. Alternatively, in another study, involving 68 cases of vesiculobullous skin lesions, pemphigus vulgaris was the most common histopathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients presenting with clinical features like vesicles and bullae, involvement of mucous membranes, Nikolsky's sign and Bulla spread sign is different in various studies conducted in India. The difference may be due to prevalence of the diseases, severity and stage of the disease at presentation and status 11,14,19 Study done by Jindal et al showed pemphigus vulgaris was the commonest vesiculobullous disorder with 31.6% cases followed by dermatitis herpentiformis with 18.3% cases. 20 In the present study the plane of separation was intraepidermal-in majority of the cases (30.30%) followed by subcorneal (28.78%) and sub epidermal planes (24.24%).…”
Section: Discussionmentioning
confidence: 99%